Density functional theory for molecular and periodic systems using density fitting and continuous fast multipole method: Stress tensor - Becker, Martin; Sierka, Marek (Journal of computational chemistry, 2019)
A full implementation of the analytical stress tensor for periodic systems is reported in the TURBOMOLE program package within the framework of Kohn–Sham density functional theory using Gaussian‐type orbitals as basis functions. It is the extension of the implementation of analytical energy gradients (Lazarski et al., Journal of Computational Chemistry 2016, 37, 2518–2526) to the stress tensor for the purpose of optimization of lattice vectors. Its key component is the efficient calculation of the Coulomb contribution by combining density fitting approximation and continuous fast multipole method. For the exchange‐correlation (XC) part the hierarchical numerical integration scheme (Burow and Sierka, Journal of Chemical Theory and Computation 2011, 7, 3097–3104) is extended to XC weight derivatives and stress tensor. The computational efficiency and favorable scaling behavior of the stress tensor implementation are demonstrated for various model systems. The overall computational effort for energy gradient and stress tensor for the largest systems investigated is shown to be at most two and a half times the computational effort for the Kohn–Sham matrix formation. © 2019 Wiley Periodicals, Inc. An implementation of analytical stress tensor in the TURBOMOLE program package within the framework of Kohn–Sham density functional theory using Gaussian‐type orbitals as basis functions is reported. Its key component is a combination of density fitting approximation and continuous fast multipole method, which allows an efficient evaluation of the Coulomb contribution. The computational efficiency and favorable scaling behavior of the implementation are demonstrated for various model systems. The overall computational effort for the energy gradient and stress tensor calculation is shown to be at most two and a half times that of a single Kohn–Sham matrix formation.